Cis-abienol from tobacco trichomes to ambergris-like compounds: advances in biosynthesis, fermentation, and industrial applications - Wang, Wenting; Zhang, Xinlong; Hu, Wei; Huang, Shen; Manzoor, Robina; Rasool, Aamir (Frontiers in Bioengineering and Biotechnology, 2026)
Cis-abienol is found in small quantities in plants like Nicotiana tabacum and Abies balsamea. It serves as a precursor for the synthesis of ambergris-like compounds, including ambroxide and ambreinolide, which are highly valued in the perfume industry for their long-lasting fixative properties and distinctive scent profile. This review summarises current progress in understanding (i) the biosynthetic pathways, chemical properties, and microbial or enzymatic degradation of cis-abienol in tobacco, particularly its production in glandular trichomes and its degradation during curing; and (ii) the chemical conversion of tobacco-derived cis-abienol and its analogues, such as sclareol, into ambrox, ambreinolide, and related fragrance compounds through oxidation, reduction, and cyclisation reactions. The bioconversion of cis-abienol or sclareol into ambergris-like compounds (AmbLCs) represents a sustainable and environmentally friendly alternative to traditional chemical methods; however, efficient biotechnological approaches for the direct biodegradation of cis-abienol into ambergris analogues remain underdeveloped. Future work should focus on metabolic engineering, enzyme discovery, and microbial pathway optimization to enhance the efficiency of these transformations, thereby laying the foundation for utilizing tobacco as a sustainable source of AmbLCs.